Does digitalization mitigate regional inequalities? Evidence from China - Haimeng Liu; Xinyang Wang; Zheye Wang; Yu Cheng (Geography and Sustainability, 2024)
Regional inequality significantly influences sustainable development and human well-being. In China, there exists pronounced regional disparities in economic and digital advancements; however, scant research delves into the interplay between them. By analyzing the economic development and digitalization gaps at regional and city levels in China, extending the original Cobb-Douglas production function, this study aims to evaluate the impact of digitalization on China’s regional inequality using seemingly unrelated regression. The results indicate a greater emphasis on digital inequality compared to economic disparity, with variable coefficients of 0.59 for GDP per capita and 0.92 for the digitalization index over the past four years. However, GDP per capita demonstrates higher spatial concentration than digitalization. Notably, both disparities have shown a gradual reduction in recent years. The southeastern region of the Hu Huanyong Line exhibits superior levels and rates of economic and digital advancement in contrast to the northwestern region. While digitalization propels economic growth, it yields a nuanced impact on achieving balanced regional development, encompassing both positive and negative facets. Our study highlights that the marginal utility of advancing digitalization is more pronounced in less developed regions, but only if the government invests in the digital infrastructure and education in these areas. This study’s methodology can be utilized for subsequent research, and our findings hold the potential to the government’s regional investment and policy-making.